OBERON3 and SUPPRESSOR of MAX2 1-like proteins form a regulatory module driving phloem development - Wallner, Eva-Sophie; Tonn, Nina; Shi, Dongbo; Luzzietti, Laura; Wanke, Friederike; Hunziker, Pascal; Xu, Yingqiang; Jung, Ilona; Lopéz-Salmerón, Vadir; Gebert, Michael; Wenzl, Christian; Lohmann, Jan U.; et al. (Nature Communications, 2023)
Spatial specificity of cell fate decisions is central for organismal development. The phloem tissue mediates long-distance transport of energy metabolites along plant bodies and is characterized by an exceptional degree of cellular specialization. How a phloem-specific developmental program is implemented is, however, unknown. Here we reveal that the ubiquitously expressed PHD-finger protein OBE3 forms a central module with the phloem-specific SMXL5 protein for establishing the phloem developmental program in Arabidopsis thaliana. By protein interaction studies and phloem-specific ATAC-seq analyses, we show that OBE3 and SMXL5 proteins form a complex in nuclei of phloem stem cells where they promote a phloem-specific chromatin profile. This profile allows expression of OPS, BRX, BAM3, and CVP2 genes acting as mediators of phloem differentiation. Our findings demonstrate that OBE3/SMXL5 protein complexes establish nuclear features essential for determining phloem cell fate and highlight how a combination of ubiquitous and local regulators generate specificity of developmental decisions in plants.